Komunikasi Antar Budaya pada Masyarakat Pendatang (Studi pada Etnis Jawa di Halong Mardika Kelurahan Rijali Kota Ambon) - Muskita, Marleen; Bakarbessy, Derek; Wairisal, Putri (Lembaga Layanan Pendidikan Tinggi Wilayah XII, 2024)
Indonesian society is known as a heterogeneous society in various aspects, such as diversity of ethnicity, religion, language and customs. Ambon City, as the capital of Maluku, has many places where migrant people can live, one of which is Jalan Mutiara Halong Mardika. The aim of the research is to find out and describe how the intercultural communication process occurs in the Javanese community in Ambon City. The method used is qualitative descriptive research, where data collection techniques use observation, interviews and documentation. The data analysis technique used uses an interactive model. The results of this research are the communication barriers that ethnic Javanese migrants usually face when interacting with local communities, namely, firstly, difficulties in the language used, meaning that when interacting with migrants, local communities mostly still use Ambonese Malay. Second, the difference in the way of communicating, in this case the rather rough accent and intonation, is in sharp contrast to the Javanese people whose way of speaking is smooth, causing them to be afraid to communicate with local people, as well as different cultural supporting factors which can be an obstacle for them when communicating with local people. . However, they were able to overcome these obstacles well so that the communication process ran well without any problems between the Javanese ethnic community and the local community.